AN ANALYSIS OF POLICIES AND LEGISLATION RELATING TO CHILD PARTICIPATION BY CHILDREN IN ALTERNATIVE CARE IN SOUTH AFRICA - Schiller, Ulene; Strydom, Marianne; Lombard, Antoinette; Rademeyer, Cobus (Social Work, 2023)
Worldwide, children in the care of the state constitute one of the most vulnerable groups in society. They are often not heard, or their views not respected in matters concerning them. This is incongruent with the Declaration of the Rights of the Child (1959) as well as the United Nations Convention on the Rights of the Child (UN, 1989). Guided by a conceptual framework of child participation theory, this article analyses South African legislation and policies to determine how and when child participation is being promoted. Findings indicate that providing information to children on how to participate meaningfully is the key for effective child participation and that practical guidelines should be developed.